Dipyridamole and vascular healing following stent implantation - Simard, Trevor; Jung, Richard; Di Santo, Pietro; Labinaz, Alisha; Short, Spencer; Motazedian, Pouya; Dhaliwal, Shan; Sarma, Dhruv; Rasheed, Adil; Ramirez, F. Daniel; Froeschl, Michael; Labinaz, Marino; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Patients undergoing coronary stent implantation incur a 2% annual rate of adverse events, largely driven by in-stent restenosis (ISR) due to neointimal (NI) tissue proliferation, a process in which smooth muscle cell (SMC) biology may play a central role. Dipyridamole (DP) is an approved therapeutic agent with data supporting improved vascular patency rates. Pre-clinical data supports that DP may enact its vasculoprotective effects via adenosine receptor-A2B (ADOR-A2B). We sought to evaluate the efficacy of DP to mitigate ISR in a pre-clinical rabbit stent model. Methods & Results 24 New Zealand White Rabbits were divided into two cohorts – non-atherosclerosis and atherosclerosis (n=12/cohort, 6 male and 6 female). Following stent implantation, rabbits were randomized 1:1 to control or oral dipyridamole therapy for 6 weeks followed by optical coherence tomography (OCT) and histology assessment of NI burden and stent strut healing. Compared to control, DP demonstrated a 16.6% relative reduction in NI volume (14.7±0.8% vs. 12.5±0.4%, p=0.03) and a 36.2% relative increase in optimally healed stent struts (37.8±2.8% vs 54.6±2.5%, p<0.0001). Atherosclerosis demonstrated attenuated effect with no difference in NI burden (15.2±1.0% vs. 16.9±0.8%, p=0.22) and only a 14.2% relative increase in strut healing (68.3±4.1% vs 78.7±2.5%, p=0.02). DP treated rabbits had a 44.6% (p=0.045) relative reduction in NI SMC content. In vitro assessment of DP and coronary artery SMCs yielded dose-dependent reduction in SMC migration and proliferation. Selective small molecule antagonism of ADOR-A2B abrogated the effects of DP on SMC proliferation. DP modulated SMC phenotypic switching with ADOR-A2B siRNA knockdown supporting its role in the observed effects. Conclusion Dipyridamole reduces NI proliferation and improves stent healing in a preclinical model of stent implantation with conventional antiplatelets. Atherosclerosis attenuates the observed effect. Clinical trials of DP as an adjunctive agent may be warranted to evaluate for clinical efficacy in stent outcomes.